PENGARUH CUSTOMER ORIENTATION DAN COMPETITIVE ORIENTATION TERHADAP CUSTOMER SATISFACTION MELALUI SALESPERSON CUSTOMER ORIENTATION - Yoga Adiyanto; Deni Sunaryo (Universitas Serang Raya, 2017)
The empirical investigation examines the influence of customer orientation and competitive orientation to customer satisfaction mediating with salesperson customer orientation in Smart Telecom company.The objective of this research was investigated the influence of customer orientation and competitive orientation to customer satisfaction mediating with salesperson customer orientation in Smart Telecom company.The design of this research using hypotheses testing in the influence of customer orientation and competitive orientation to customer satisfaction mediating with salesperson customer orientation in Smart Telecom company came from of 300 customers as respondent drawing on influence marketing literature, the authors empirically test a model was Pearson coefficient correlation and AMOS with SEM methods.The result of this research conclude that there are influences of customer orientation and competitive orientation to customer satisfaction mediating with salesperson customer orientation in Smart Telecom company. The effects of customer orientation and competitive orientation to customer satisfaction in customer are also verified